Pengaruh Kualitas Pelayanan, Sanksi dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Jepara - Muhammad Sukron Iriyanto; Fatchur Rohman (Jurnal Rekognisi Akuntansi, 2022)
The research conducted is quantitative. The data used in this research are subjective data. The source of data in this research is primary data. This study uses a quantitative method in the form of survey assessment in KPP Pratama Jepara. This study aims to determine the effect of service quality, tax sanctions and tax rates on UMKM taxpayer compliance in Jepara. The number of population used is based on MSME taxpayers registered at KPP Pratama Jepara, which is as many as 11,548 taxpayers. While the sample used is UMKM taxpayers who report the Annual SPT which amounted to 3,974. From the results of calculations using the Slovin formula, the number of taxpayers used as a sample is 97.54 or 100 Individual Taxpayers of Micro, Small and Medium Enterprises (UMKM). In this study, the method used to take samples using purposive sampling technique. The data analysis method used is multiple linear regression analysis with data analysis test consisting of data quality analysis and classical assumption test. In testing the hypothesis using the coefficient of determination test and statistical test f and statistical test t. Service quality has a positive and significant effect on taxpayer compliance in paying taxes at the Jepara KPP Pratama. Tax sanctions have a positive and significant effect on taxpayer compliance in paying taxes at KPP Pratama Jepara. Tax rates have a significant negative effect on taxpayer compliance in paying taxes at KPP Pratama Jepara.